Déjà vu? Short-term training in Germany 1980 - 1992 and 2000 - 2003 - Bernd Fitzenberger; Olga Orlyanskaya; Aderonke Osikominu; Marie Waller (Institute for the Study of Labor (IZA), 2008)
Short-term training has recently become the largest active labor market program in Germany regarding the number of participants. Little is known on the effectiveness of different types of short-term training and on their long-run effects. This paper estimates the effects of short-term training programs in West Germany starting in the time period 1980 to 1992 and 2000 to 2003 regarding the two outcomes employment and participation in longer training programs. We find that short-term training shows mostly persistently positive and often significant employment effects. Short-term training focusing on testing and monitoring search effort shows slightly smaller effects compared to the pure training variant. The lock-in periods lasted longer in the 1980s and 1990s compared to the early 2000s. Short-term training results in higher future participation in longer training programs and this effect was much stronger for the earlier time period.
urn:nbn:de:101:1-20080613131
Keywords: C14; 330; Short-term training; employment effects; future training participation; administrative data; active labor market programs; Arbeitsmarktpolitik; Weiterbildung; Arbeitsuche; Berufliche Integration; Wirkungsanalyse; Beschäftigungseffekt; Deutschland